MIDDLE JURASSIC NAUTILOIDEA FROM WESTERN FRANCE (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
The Middle Jurassic shelf margin limestones and marly limestones of Western France yield quite numerous Nautilida. This record is here described for the first time in detail, nine genera and more than forty species, whose range rarely exceeds one or two ammonite biozones, constitute a rather precise tool to date Middle Jurassic beds. Each taxon is placed in an accurate biostratigraphical chart; a new genus, Pictonautilus nov. gen., is described. The stratigraphical range of Cenoceras, Digonioceras and Gen. B n. ? (sensu Chirat 1997) is extended up to the Middle Callovian. In the Jurassic successions of Poitou, Nautilida always represent a minor part of the fossil record, they are more abundant in four levels: Middle Aalenian, base of Upper Bajocian, Lower Bathonian and top of Middle Bathonian. Dwarf Nautilida (Paracenoceras) and species showing more folded septa and a subventral siphuncle (Pseudaganides) or strongly ribbed specimens (Cymatonautilus) are characteristic of stable open-shelf environments (Callovian), whereas large shelled nautilus would be mostly present during deepening episodes. The geographical extension of many taxa indicates a provincialism that fits with that of ammonites of the same period.